COVID-19 susceptibility, severity, and vaccine effectiveness in patients with psoriasis: a nationwide cohort study in South Korea - Young Ah Cho; Hyein Han; Sungho Won; Ji Won Lim; Jae Young Sung; Chang Yong Kim; Da-Ae Yu; Yang Won Lee; Yong Beom Choe (Scientific Reports)
Abstract Patients with psoriasis are vulnerable to infections due to dysregulated immunity, use of immunosuppressive drugs, and comorbid conditions. Despite ongoing concerns regarding coronavirus disease 2019 (COVID-19) vulnerability in patients with psoriasis, evidence remains limited. This nationwide, population-based, retrospective cohort study aimed to assess the risk and severity of COVID-19 and vaccine effectiveness in patients with psoriasis, including those receiving immunomodulatory therapy, using Korean National Health Insurance Service claims data from 2018 to 2021. The primary analysis included 167,746 patients with psoriasis and 866,582 controls, revealing no significant associations between psoriasis and COVID-19 (adjusted hazard ratio [aHR]: 0.99, 95% confidence interval [CI]: 0.95–1.04). Conversely, the secondary analysis of 3,131 patients with psoriasis and 265,475 controls revealed significantly higher rates of severe COVID-19 in patients with psoriasis (aHR: 1.33, 95% CI: 1.08–1.64). While some treatment subgroups — such as the cyclosporine and methotrexate subgroups — demonstrated higher incidences of COVID-19 than the reference (nonsystemic) subgroup, these differences were not statistically significant. Furthermore, vaccine interaction effects between the duration of immunity and psoriasis or each treatment were insignificant (all P > 0.05). Patients with psoriasis exhibited a higher risk of severe COVID-19; however, their COVID-19 susceptibility and vaccine effectiveness resembled those of the control group. Additionally, the use of immunomodulatory agents did not impact COVID-19 risk or vaccine effectiveness. These findings highlight the need for dermatologists to implement pre- and postinfection strategies tailored for patients with psoriasis.